Genotype–phenotype study of familial haemophagocytic lymphohistiocytosis type 3. Issue 5 (19th January 2011) - Sieni, Elena; Cetica, Valentina; Santoro, Alessandra; Beutel, Karin; Mastrodicasa, Elena; Meeths, Marie; Ciambotti, Benedetta; Brugnolo, Francesca; zur Stadt, Udo; Pende, Daniela; Moretta, Lorenzo; Griffiths, Gillian M; et al.
Abstract : Background: Mutations of UNC13D are causative for familial haemophagocytic lymphohistiocytosis type 3 (FHL3; OMIM 608898). Objective: To carry out a genotype–phenotype study of patients with FHL3. Methods: A consortium of three countries pooled data on presenting features and mutations from individual patients with biallelic UNC13D mutations in a common database. Results: 84 patients with FHL3 (median age 4.1 months) were reported from Florence, Italy (n=54), Hamburg, Germany (n=18), Stockholm, Sweden (n=12). Their ethnic origin was Caucasian (n=57), Turkish (n=10), Asian (n=7), Hispanic (n=4), African (n=3) (not reported (n=3)). Thrombocytopenia was present in 94%, splenomegaly in 96%, fever in 89%. The central nervous system (CNS) was involved in 49/81 (60%) patients versus 36% in patients with FHL2 (p=0.001). A combination of fever, splenomegaly, thrombocytopenia and hyperferritinaemia was present in 71%. CD107a expression, NK activity and Munc 13-4 protein expression were absent or reduced in all but one of the evaluated patients. 54 different mutations were observed, including 15 new ones: 19 missense, 14 deletions or insertions, 12 nonsense, nine splice errors. None was specific for ethnic groups. Patients with two disruptive mutations were younger than patients with two missense mutations (p<0.001), but older than comparable patients with FHL2 (p=0.001). Conclusion: UNC13D mutations are scattered over the gene. Ethnic-specific mutations were not identified. CNS involvement is more common than in FHL2; in patients with FHL3 and disruptive mutations, age at diagnosis is significantly higher than in FHL2. The combination of fever, splenomegaly, thrombocytopenia and hyperferritinaemia appears to be the most easily and frequently recognised clinical pattern and their association with defective granule release assay may herald FHL3.